Relative sea level changes during the Last Glacial Maximum and deglaciation (33–15 ka) inferred from the δ18O records of planktic foraminifera from the Sea of Japan. (1st March 2022) - Gorbarenko, Sergey A.; Shi, Xuefa; Bosin, Aleksandr A.; Liu, Yanguang; Artemova, Antonina V.; Zou, Jianjun; Yanchenko, Elena A.; Vasilenko, Yuriy P.; Wu, Yonghua; Vladimirov, Anton S.
Abstract: The Sea of Japan, located in the humid zone, was subjected to significant freshening of surface waters and a decrease in ventilation of deep waters during the glacial eustatic drop in relative sea level (RSL) and a decrease in water exchange with Pacific due to the shallowness of its straits. As a result, the δ 18 O values of planktic foraminifera (δ 18 Opf ) decreased by several ppm, in contrast to the increase of ones in the Red Sea, depending on the degree of RSL drop. The good preservation of planktic foraminifera in the sediments of the Sea of Japan during the Last Glacial Maximum (LGM) and deglaciation allows us to significantly refine and supplement the available evidences of the global sea level changes over the 33–15 ka. Based on the obtained and published records of δ 18 Opf of five cores from different parts of the sea and the general chronology of the accumulation of dark layers in the sediments of the Sea of Japan, we calculated the δ 18 Opf stacks with high and low resolution (0.13 kyr for two cores and 0.5 kyr for other three cores) for the time 33–15 ka. Both stacks showed significant RSL falls at the onset of LGM (32–29 ka), during 21.8–20.3 ka, and an abrupt rise at 17 ka consistently with previously published data. The higher resolution stack additionally showed two phases of RSL falls at the onset of the LGM followed by a slow decrease until 22 ka, with a short and abrupt descent at around 25 ka. According to both stacks the lowest sea level around 18.5–17.5 ka was preceded by a short rise just before 19 ka. A significant RSL rise at 17 ka was followed by an abrupt and short fall at nearly 16.5 ka and then prolonged rise since around 16.2 ka. Highlights: Two stacks of planktic foraminifera δ 18 O records were calculated over the 33-15 ka with a higher and lower resolution. Chronology was based on synchronicity of dark layers formation ruled by surface water salinity and ventilation changes. Both stacks showed significant relative sea level (RSL) falls at 32–29 ka, during 21.8-20.3 ka, and abrupt rise at 17 ka. A higher resolution stack additionally showed millennial-centennial RSL changes over Last Glacial Maximum and since 17 ka.